The Unintended Consequence of Land Finance: Evidence from Corporate Tax Avoidance - Chen, Tao; Tan, Youchao; Wang, Jinghua; Zeng, Cheng (Colin) (Management Science, 2022)
Using a large sample of unlisted industrial firms in China, we find that a decrease in local governments’ land transfer revenues leads to lower tax avoidance by firms within their jurisdiction. Our cross-sectional variation tests suggest that the tax-avoidance-reduction effect is stronger in cities with higher land finance dependence and government intervention, as well as where the political leaders have stronger promotion incentives. However, the effect is moderated for politically connected firms. Further analysis reveals that intensified tax enforcement is the mechanism through which land transfer revenue losses result in decreased tax avoidance. Our study offers novel evidence on a previously underexplored determinant of corporate tax avoidance through the lens of land finance. This paper was accepted by Gustavo Manso, finance. Funding: The authors acknowledge financial support from the National Natural Science Foundation of China [Grants 72002105, 71972089 and 72132002]. T. Chen is grateful for the financial support from the Singapore Ministry of Education Academic Research Fund [Grant 2015-T2-1-118, RG166/18] and the Natural Science Foundation of Guangdong Province, China [Grants 2018A03031043 and 2019A1515011635]. C. (C.) Zeng acknowledges the start-up research fund from the Hong Kong Polytechnic University [Grant A0035237]. Supplemental Material: Data and the online appendix are available at https://doi.org/10.1287/mnsc.2021.4191 .